Media and Muslim societies during the time of Islamic revivalism (1800s-1950s) - Shafizan Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The decline of Islamic empires, most notably the Ottoman Empire, in the late 1800s and early 1900s proved to be a watershed moment in the development of modern Muslim societies. Western civilizations with their secular, modern, and exploitative ideas encroached on Muslim lands, beliefs, and way of life. Muslims who found themselves at a crossroads between the eventual collapse of their own political structure and the disputable, yet attractive prospects of Western modernism faced a revivalism that drove them to re-examine their place in a Westernizing and modernising world. The availability of publishing technology, as well as exposure to new ideas, aided in the dynamic changes occurring in Muslim societies during this time period. This article examines how Muslim societies responded to these developments in the past, and how the media played a critical role in their attempt to endure Western colonial threats while maintaining their Islamic beliefs.